The Recent Performance of the UK Labour Market. - Nickell, S; Quintini, G (2002)
We consider both the overall macroeconomic performance of the UK labour market since 1997, as well as some of the underlying micro problems, particularly those facing unskilled workers, On the macro front, we have seen unemployment decline to its lowest level for a generation without excessive inflationary pressure. The main factors behind this decline in equilibrium unemployment stem from actions taken by the previous government. Changes introduced in the labour market since 1997 are likely to have only small effects on equilibrium unemployment. Underlying this favourable aggregate labour-market performance are serious problems facing unskilled men who have seen dramatic increases in their unemployment and inactivity rates, concentrated particularly in Wales and the northern regions of Britain. The policy response since 1997 has focused on encouraging the unskilled into work (the New Deal) while simultaneously raising the rewards for working (the minimum wage, tax credits). These policies have had a positive impact on youth employment and have significantly reduced child poverty. So far, however, existing policies do not seem likely to have a serious impact on the high levels of worklessness among unskilled men.